Return spillovers between Islamic and conventional banking rates: Evidence from emerging Islamic countries - Remzi Gök; Shawkat Hammoudeh; Ahdi Noomen Ajmi; Mehmet Balcilar (Borsa İstanbul Review, 2025)
This study examines return connectedness and spillover shock effects between Islamic profit-sharing rates (PSR) and conventional deposit rates (DPR) of banking sectors across various maturities in Türkiye and Malaysia. Overall, financing rates with various maturities in Türkiye act as transmitters of shocks in both banking sectors. Specifically, short-term rates serve as net spillover transmitters, while long-term rates of DPR and PSR emerge as primary transmitters and receivers, respectively. Total directional connectedness analysis reveals that the degree of integration between sectors fluctuates over time, with political instability and monetary policy actions being key drivers. Although conventional deposit rates dominate their Islamic counterparts in the early part of the study period, a significant policy rate hike in 2014 shifts this balance in favour of profit-sharing rates, suggesting that the conventional banking sector has become increasingly susceptible to shocks originating from the Islamic banking sector in recent years. Moreover, Türkiye's adoption of unconventional monetary policies has reduced integration within the banking system, thereby altering the dynamics of return spillovers, with deposit rates acting as main transmitters. We observe a relatively stable connectivity mechanism over time in Malaysia, where market risk becomes stronger as of 2020. Both short-term rates are net transmitters during most of the sample period, and medium- and longer-term tenors of the Islamic (conventional) banking sector function as net receivers (transmitters). DPR is shown to exert a substantial influence over PSR, with spillover shock effects being more pronounced for shorter tenors. While global factors strongly influence overall connectivity in Türkiye, local factors such as exchange rates, interest rates, and credit default swaps (CDS) play a critical role in net shock transmission. DPRs are shown to be dominant factors in predicting PSRs in Türkiye and both sectors exhibit stronger interactions at higher intervals of time.
Keywords: 330; Connectedness; Deposits; Islamic banks; Spillover; Wavelet causality